The ripe pulp of Mangifera indica L.: a rich source of phytosterols and other lipophilic phytochemicals - Vilela, Carla (2021)
The chemical composition of the lipophilic extracts of the ripe pulp of mangoes from twelve cultivars of Mangifera indica L. from Madeira Island was investigated by gas chromatography–mass spectrometry (GC–MS) for the first time. The ripe pulp of these mango cultivars showed analogous amounts of lipophilic extractives, as well as sim ilar qualitative chemical compositions. The predominant compounds were free and glycosylated sterols and fatty acids, representing 44.8–70.7% and 22.6–41.9%, respectively, of the total amount of lipophilic components. Small er amounts of long chain aliphatic alcohols and α-tocopherol were also identified. These data indicate that the investigated mango cultivars are a rich source of valuable phytochemicals, contributing to the intake of at least 9.5–38.2 mg of phytosterols (free and glycosylated) and 0.7–3.9 mg of fatty acids (ω−3 and ω−6) per 100 g of fresh mango, with recognizable beneficial effects on human nutrition and health.